2021
DOI: 10.3390/plants10122558
|View full text |Cite
|
Sign up to set email alerts
|

Global Innovation Trends for Plant-Based Vaccines Production: A Patent Analysis

Abstract: The use of plants as biofactories for the production of medical products and vaccines has a long history, but the recent COVID-19 pandemic has caused this set of technologies, for their potential to contribute to the development of innovative solutions for tackling pandemic spread worldwide, to rise in prominence. The purpose of this paper is to analyze the global innovation scenario of plant-based vaccine production. Methods: Patent search using a specific set of technical classification codes and keywords wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Furthermore, we determine, through different patent databases, publication dates, applicants, owners, patent classifications, and patent jurisdictions. This type of research has already been demonstrated in various fields through several recent publications on hydrogel-based coatings [9], biocontrol agents [10], bioinks [11], energy [12,13], carbon [14], plant-based vaccines [15], and orthosis [16].…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, we determine, through different patent databases, publication dates, applicants, owners, patent classifications, and patent jurisdictions. This type of research has already been demonstrated in various fields through several recent publications on hydrogel-based coatings [9], biocontrol agents [10], bioinks [11], energy [12,13], carbon [14], plant-based vaccines [15], and orthosis [16].…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, the coronavirus disease 2019 (COVID-19) pandemic scenario led to the accelerated generation of pioneering plant-made vaccines capable of dealing with this international health issue. Some of the most representative corporations involved in this pursuit are Medicago Inc., GlaxoSmithKline, iBio Inc., and Kentucky BioProcessing [ 63 ]. For example, once the SARS-CoV-2 spike protein sequence became available, Medicago Inc. generated the VLP vaccine candidates in just 20 days [ 47 ].…”
Section: Overview Of the Present Landscape Of Plant-based Vaccinesmentioning
confidence: 99%
“…En general, el uso de plantas para producir biomoléculas es un área de investigación innovadora que se inició a principios de la década de 1990 bajo el nombre de biopharming o agricultura molecular de plantas, entendida como el uso de plantas modificadas genéticamente para producir una amplia gama de productos farmacéuticos e industriales (Frisio & Ventura, 2021). Aunque desde hace varios años se ha trabajado de manera extensiva respecto a la investigación y desarrollo de vacunas en plantas y se han obtenido algunos resultados muy favorables para la protección contra distintas enfermedades, hoy en día las vacunas vegetales tanto para uso veterinario como humano siguen sin encontrarse disponibles en el mercado debido a las estrictas regulaciones impuestas por entidades como la Food and Drug Administration (FDA).…”
Section: ¿Desde Cuándo Se Fabrican Vacunas a Partir De Plantas?unclassified
“…A nivel global, los datos muestran que el número de solicitudes de patentes respecto a estas tecnologías se mantuvo bastante constante hasta el año 2015. Desde entonces, las solicitudes de patentes han crecido constantemente y casi se duplicaron desde el periodo 2011-2015 (33 familias de patentes) al período 2016-2020 (60 familias), sin embargo, los datos del 2020 se consideran como incompletos debido al tiempo transcurrido entre la solicitud de patente y la publicación (Frisio & Ventura, 2021). Hasta el momento la única vacuna generada en plantas que ha sido aprobada es contra la enfermedad de Newcastle en aves de corral, se expresa en células de tabaco en suspensión y se aprobó en 2004 (Takeyama, N. et al, 2015).…”
Section: ¿Desde Cuándo Se Fabrican Vacunas a Partir De Plantas?unclassified